2021
DOI: 10.1590/1807-1929/agriambi.v25n12p801-806
|View full text |Cite
|
Sign up to set email alerts
|

Field estimate with NDVI of grain yield and quality of wheat flour

Abstract: Nitrogen fertilization is essential for wheat yield and quality but needs more accuracy, and the use of proximal optical sensors in the field can assist in this goal. This study aimed to verify if it is possible to use the normalized difference vegetation index (NDVI) obtained throughout the wheat growth phase to estimate the grain yield and the technological quality of the flour from cultivars submitted to nitrogen doses. The experiment was conducted at field conditions in Ponta Grossa, PR, Southern Brazil. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…This difference occurred, for instance, when there were different levels of carotenoids [17,18]. When studying wheat crops, researchers found that the NDVI values among cultivars were influenced by the phenological stages of the crop and the amount of nitrogen present in the soil [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…This difference occurred, for instance, when there were different levels of carotenoids [17,18]. When studying wheat crops, researchers found that the NDVI values among cultivars were influenced by the phenological stages of the crop and the amount of nitrogen present in the soil [44,45].…”
Section: Discussionmentioning
confidence: 99%